PELAKSANAAN PELAYANAN KESEHATAN GERIATRI BAGI NARAPIDANA LANJUT USIA DI LEMBAGA PEMASYARAKATAN DENGAN PEMERIKSAAN RUTIN - Neva Gledy Fadhila (Journal Publicuho, 2020)
This paper aims to determine the provision of geriatric health services to elderly prisoners. This study uses a descriptive qualitative approach, the data collected by researchers by conducting field studies is conducting interviews with several correctional officers to obtain data through interviews, field studies and literature reviews in explaining the provision of geriatric health services to elderly prisoners. The results showed that service delivery was constrained by costs, facilities and infrastructure as well as a lack of human resources who were experts in the health sector. Elderly prisoners do not get the geriatric care that should be done so that elderly prisoners receive treatment and prevention of diseases and health problems due to ageing. This can be handled by carrying out routine checks on inmates. Not only examinations but also counselling activities about the health experienced by elderly prisoners. This examination is carried out by the prison in collaboration with the regional health office and is carried out regularly every week. With this routine check-up, elderly prisoners can overcome their health problems and prevent diseases that usually attack a person due to ageing.